PERFORMANCE ANALYSIS OF GOVERNMENT INTERNAL SUPERVISORY APPARATUS AT THE INSPECTORATE OF CENTRAL PAPUA PROVINCE - Kopong, Agustina; Rantererung, Corvis L; Lambe, Kristian H.P (Indonesian Journal Of Economy Studies, 2024)
This study focuses on the object of research at the Inspectorate of Central Papua Province, specifically on the performance of the Government Internal Supervisory Apparatus (APIP) in the Inspectorate of Central Papua Province. The Government Internal Supervisory Apparatus (APIP) plays a strategic role in ensuring accountability and transparency in the management of regional finances and resources. This study aims to assess and analyze the performance of the Government Internal Supervisory Apparatus at the Inspectorate of Central Papua Province. The research object is located at the Inspectorate of Central Papua Province. This type of research employs a qualitative approach. The data sources include primary and secondary data. Data collection methods consist of observation, interviews with informants, and documentation. The informants in this study are 8 (nine) employees at the Inspectorate of Central Papua Province who serve as members of the Government Internal Supervisory Apparatus. The data analysis method used is qualitative descriptive analysis, which includes data collection, data reduction, data presentation, and drawing conclusions.The study concludes that the performance of APIP at the Inspectorate of Central Papua Province plays a crucial role in ensuring good, accountable, and transparent governance. APIP serves as an independent control mechanism, helping to create effective, efficient, and accountable governance in Central Papua Province. Optimal performance from APIP will contribute to the improvement of governance and public trust in governmental institutions. Supporting factors, including adequate budgeting, sufficient human resources, facilities and infrastructure, leadership commitment, and good benefits and allowances, significantly influence the performance of the Government Internal Supervisory Apparatus (APIP) at the Inspectorate of Central Papua Province. Conversely, factors hindering APIP's performance at the Inspectorate of Central Papua Province, such as a lack of human resource competence, a non-supportive organizational culture, low motivation, and a limited number of auditors, greatly affect APIP's ability to carry out supervisory tasks effectivelyKeyword:Â Performance, Government Internal Supervisory Apparatus, and InspectorateÂ Â